Heat-killed Mycobacterium bovis-bacillus Calmette Guerin-suppressed total serum IgE response in ovalbumin-sensitized newborn mice - (:unkn) unknown (MARCEL DEKKER INC, 2000)
To determine the impact of bacillus Calmette Guerin (BCG) vaccination on IgE production in ovalbumin (OVA)-sensitized newborn mice, four groups (I, II, III, IV) of BALB/c mice were immunized on the first day of life with live BCG, killed BCG, BCG diluent, and saline, respectively. No injection was applied to mice in group V (control). All mice except group V were sensitized and challenged with OVA in the fourth and sixth weeks, respectively, and serum total IgE levels were determined at 8 weeks, 2 weeks after the second OVA challenge. IgE levels of all groups were significantly higher than the control group except for group II (p = 0.95). Mice in group II showed significantly lower IgE values than group, IV and I (p = 0.007 and p = 0.003, respectively). We concluded that heat-killed BCC may downregulate IgE response to OVA in newborn mice.
Keywords: heat-killed BCG; mice; IgE; T-HELPER; PREVALENCE; ASTHMA; SYMPTOMS; TH1; CHILDREN; CELLS